Rothmund-Thomson syndrome in a 6-year-old little girl. - Mun, A.; Nizamova, D.; Kobiljonova , D. (European Journal of Pediatric Dermatology, 2025)
Rothmund-Thomson syndrome (RTS) is a rare and severe autosomal recessive disorder characterized by dermatological lesions prevalent in photoexposed areas, associated with alterations of other organs, especially the skeletal system, and neoplastic complications. Dermatological lesions are early and allow to suspect the diagnosis, but RTS is a multisystem disease that requires a multidisciplinary approach, starting from genetic investigation. A case is presented in a 6-year-old girl, in whom genetic investigation showed a compound heterozygosity on the RECQL4 gene.